1891 N.H. Pub. Stat. 332 - (:unkn) unknown (My University, 1891)
Ch. 117, § 7: Regulated the sale of gunpowder less than twenty-five pounds and sales in the night with a fine of not more than five dollars.
Keywords: TRANSFER, MANUFACTURE & STORAGE OF GUNPOWDER